Agent-based models of bounded rationality. Issue 1 (14th March 2017) - Secchi, Davide
Abstract : Purpose: The purpose of this editorial is to introduce the Special Issue "Agent-Based Models of Bounded Rationality" and to provide an overview of its rationale and main objectives. Design/methodology/approach: After outlining the overall framework to justify the choice of agent-based modeling in relation to bounded rationality, an overview of the six papers published in the Special Issue is presented. Findings: The paper argues that simulation of complex adaptive social systems is a way to set the ground for updating the concept of bounded rationality and prepare for it to still play a significant role in the years to come. Originality/value: After its introduction, bounded rationality remained mostly used but seldom discussed in both its assumptions and its meaning. The originality of this introduction is to unveil some of the points that keep rationality still at the core of organization and team research.